Angiosarcoma of an Arteriovenous Fistula for Hemodialysis in a Kidney Transplant Recipient Affected by Lowe's Syndrome. (13th April 2020) - D'Ambrosio, V.; Silvestri, P.; Aureli, F.; Sturniolo, A.; Grandaliano, G.; Ferraro, P. M.
Abstract : Objective/Background . To describe an uncommon, life-threatening condition such as angiosarcoma of a fistula for hemodialysis occurring in a transplant recipient affected by Lowe's syndrome. Summary . We present the case of a 56-year-old male kidney transplant recipient affected by Lowe's syndrome, also known as oculocerebrorenal syndrome, a rare X-linked disorder characterized by congenital cataracts, hypotonia, intellectual disability, and Fanconi-like renal tubular dysfunction, who was diagnosed with angiosarcoma of a functioning arteriovenous fistula for hemodialysis. Conclusion . Angiosarcoma is a rare soft tissue tumor, and only 22 cases of angiosarcoma of arteriovenous fistulae were described so far; although a correlation between Lowe's syndrome and a higher risk of tumor compared to the general population has not been described so far, the mechanisms of disease causation could be an interesting starting point for future studies on a possible connection between the two events.